2009
DOI: 10.1099/mic.0.029132-0
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of protease-activated receptors on an immortalized oral epithelial cell line by Porphyromonas gingivalis gingipains

Abstract: Porphyromonas gingivalis activates protease-activated receptors (PARs) on oral keratinocytes, resulting in downstream signalling for an innate immune response. Activation depends on P. gingivalis gingipains, but could be confounded by lipopolysaccharide signalling through Toll-like receptors. We therefore hypothesized that P. gingivalis cleaves oral keratinocyte PARs in an Arg-(Rgp) or Lys-(Kgp) gingipain-specific manner to upregulate pro-inflammatory cytokines. Immortalized human oral keratinocytes (TERT-2) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 45 publications
2
39
0
6
Order By: Relevance
“…Gingipains have been shown to activate PAR2 in immune inflammatory cells and in cells from the oral epithelial barrier, leading to increased production of proinflammatory mediators (4,8,10,(33)(34)(35) and activation of signaling pathways associated with increased inflammatory responses (36). In addition, neutrophil protease 3 was also shown to activate host cells through PAR2, inducing the release of proinflammatory cytokines (6), which not only have a direct effect on periodontal destruction but can also act indirectly by upregulating MMP expression (37,38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gingipains have been shown to activate PAR2 in immune inflammatory cells and in cells from the oral epithelial barrier, leading to increased production of proinflammatory mediators (4,8,10,(33)(34)(35) and activation of signaling pathways associated with increased inflammatory responses (36). In addition, neutrophil protease 3 was also shown to activate host cells through PAR2, inducing the release of proinflammatory cytokines (6), which not only have a direct effect on periodontal destruction but can also act indirectly by upregulating MMP expression (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…PAR2 activation-associated enhanced biosynthesis of proinflammatory mediators has been well established (4)(5)(6)(7)(8)(9)(10). A previous study by our group demonstrated that PAR2 mediates host cell mechanisms responsible for increased levels of prostaglandin E2, gamma interferon, interleukin-␤ (IL-1␤), and IL-6 and for the resulting increased alveolar bone loss in a periodontitis model of P. gingivalis infection in mice (8).…”
mentioning
confidence: 99%
“…Although it has been reported that different mammalian and prokaryotic proteases can activate PARs (e.g., human trypsin [55,56] or Porphyromonas gingivalis gingipains [57]), different forms of these receptors exhibit specificities for various activating proteases (e.g., PAR2 can be activated by trypsin but not by thrombin). Additionally, most studies investigating how microbes disrupt the intestinal epithelium via PAR activation have focused on pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…In response to L. monocytogenes , epithelial cells release IL-1α and, in an IL-1RI-dependent manner, modulate autonomous resistance to these invasive enteric pathogens. Other invasive mucosal pathogens including C. albicans 23 and Porphyromas gingivalis 25,28,29 also induce the release of IL-1α from oral keratinocytes over time, suggesting that the epithelial response to pathogens could be generalized.…”
Section: Discussionmentioning
confidence: 99%